2021
DOI: 10.4300/jgme-d-20-00722.1
|View full text |Cite
|
Sign up to set email alerts
|

Defeating Unconscious Bias: The Role of a Structured, Reflective, and Interactive Workshop

Abstract: Background Unconscious or implicit biases are universal and detrimental to health care and the learning environment but can be corrected. Historical interventions used the Implicit Association Test (IAT), which may have limitations. Objective We determined the efficacy of an implicit bias training without using the IAT. Methods From April 2019 to June 2020, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Recently, an interactive workshop on implicit biases was evaluated for medical students, residents, and faculty. The study found significant improvements in knowledge and perceptions on bias [ 33 ]. A workshop on implicit biases regarding Hispanic patients was tested among first year medical students, and found improvement in implicit association tests among some of the students [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an interactive workshop on implicit biases was evaluated for medical students, residents, and faculty. The study found significant improvements in knowledge and perceptions on bias [ 33 ]. A workshop on implicit biases regarding Hispanic patients was tested among first year medical students, and found improvement in implicit association tests among some of the students [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implement specialized anti-bias training for those involved in the recruitment, interviewing, evaluation, and selection processes, in addition to the general anti-bias and cultural humility education that should exist at any institution 93. These training sessions should ideally be interactive, practical, expert-led, and tailored for the specific context or practice; simple click-through, self-study modules are not enough 94…”
Section: Programmatic Interventionsmentioning
confidence: 99%
“…Bias affects our perceptions of another's knowledge, ability, professionalism, and readiness for independent practice. 2 Over repeated assessments, these biases can result in an amplification cascade, 1 a phenomenon in which small differences in assessed performance lead to larger differences in grades and selection for awards, favoring well-represented individuals and hindering underrepresented in medicine (UiM) trainees in achieving training success. 3 Eliminating harmful effects of cognitive biases requires a multilevel response.…”
Section: What Is Knownmentioning
confidence: 99%
“…5 How You Can Start TODAY Training should facilitate faculty recognition of their own biases, teach faculty to recognize biased language in their own narrative assessments, and provide skills to counter biased thinking. 2 Create an awareness of how bias influences trainee assessment and the significance of the amplification cascade. 4.…”
Section: What Is Knownmentioning
confidence: 99%